CeO2 modified current collector, preparation method and application thereof, and sodium ion battery

By coating CeO2 nanowires and binder on the current collector of the sodium ion battery, the CeO2 layer is formed, and the problem of sodium metal dendrites in sodium ion battery is solved, the cycle and high temperature performance of the battery is improved, and the battery is extended Service life.

CN119208617AInactive Publication Date: 2024-12-27JIANGSU PYLON BATTERY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411324719.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing negative-electrode sodium ion batteries are prone to form uneven sodium dendrites during the sodium metal deposition process, resulting in diaphragm puncture and short circuit, affecting the cycling and safety performance of the battery.

Method used

The CeO2-modified current collector is used to coat CeO2 nanowires and binder on the current collector to form a CeO2 layer, which improves the mechanical properties and conductivity of the negative electrode, reduces the growth of sodium metal dendrites, and enhances the cycle stability of the battery.

Benefits of technology

It effectively reduces the formation of sodium metal dendrites, improves the cycle life and high temperature performance of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208617A_ABST
    Figure CN119208617A_ABST
Patent Text Reader

Abstract

The invention provides a CeO2 modified current collector, a preparation method and application thereof, and a sodium ion battery, and relates to the technical field of batteries. The CeO2 modified current collector provided by the invention comprises a current collector and a CeO2 layer coated on the current collector, the CeO2 layer comprises a CeO2 nanowire and a binder; the mass ratio of the CeO2 nanowire to the binder is 96%-99%. The research of the inventor finds that when the CeO2 modified current collector is applied to the negative-electrode-free sodium ion battery, the mechanical property of a pole piece can be improved, so that the negative electrode does not generate electric separation under the action of volume expansion stress, the probability of volume expansion caused by dendritic crystals formed by sodium metal is effectively reduced, and the cycle life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a CeO2-modified current collector, a preparation method and application thereof, and a sodium ion battery. Background Art

[0002] The advantages of sodium-ion batteries are that sodium resources are abundant and the price is lower than that of lithium-ion batteries. Now the introduction of negative electrode-free sodium-ion batteries has made the cost of sodium-ion batteries lower. Since negative electrode-free batteries have relatively high requirements for the uniformity and thickness of metallic sodium deposited on the negative electrode surface, existing negative electrode-free sodium-ion batteries have the problem of sodium dendrites forming on the negative electrode surface, piercing the diaphragm and causing a short circuit. Therefore, it is necessary to modify the current collector to improve its electrical properties and safety performance. Many scholars have modified high-entropy metal nanoparticles on the current collector. The high-entropy nanoparticles have sodium affinity, which can reduce the potential for sodium metal formation, inhibit the growth of sodium dendrites and improve its cycle performance; some surfaces are coated with an aluminum foil layer with an aluminum-tin alloy film layer, which can make the battery have the characteristics of good structural flatness, strong processing controllability and high cycle stability.

[0003] However, there is still little research on current collector modification, and the improvement effect is not ideal, which needs further research.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The first object of the present invention is to provide a CeO2 modified current collector to solve the above technical problems.

[0006] The second object of the present invention is to provide a method for preparing the above-mentioned CeO2 modified current collector.

[0007] The third object of the present invention is to provide the use of the above-mentioned CeO2-modified current collector in the preparation of sodium ion batteries.

[0008] A fourth object of the present invention is to provide a sodium ion battery.

[0009] In order to achieve the above objectives, the following technical solutions are adopted:

[0010] In a first aspect, the present invention provides a CeO2-modified current collector, comprising a current collector and a CeO2 layer coated on the current collector;

[0011] The CeO2 layer includes CeO2 nanowires and a binder;

[0012] The mass proportion of CeO2 nanowires in the CeO2 layer is 96%-99%.

[0013] As a further technical solution, the diameter of the CeO2 nanowire is 2-6nm, and the aspect ratio is 100-500.

[0014] As a further technical solution, the binder includes PVDF.

[0015] As a further technical solution, the coating density of the CeO2 layer is 6 to 8 g / cm 2 .

[0016] As a further technical solution, the current collector includes aluminum foil or carbon-coated aluminum foil.

[0017] In a second aspect, the present invention provides a method for preparing the above-mentioned CeO2 modified current collector, comprising: preparing a slurry containing CeO2 nanowires and a binder, then coating the slurry on the current collector, and preparing the CeO2 modified current collector after drying.

[0018] As a further technical solution, the slurry also contains a dispersant;

[0019] The dispersant includes NMP.

[0020] In a third aspect, the present invention provides the use of the above-mentioned CeO2-modified current collector in the preparation of a sodium ion battery.

[0021] In a fourth aspect, the present invention provides a sodium ion battery using the above-mentioned CeO2 modified current collector as the negative electrode.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The CeO2-modified current collector provided by the present invention comprises a current collector and a CeO2 layer coated on the current collector, wherein the CeO2 layer is mainly composed of CeO2 nanowires and a binder. CeO2 has an extremely high aspect ratio, good electrical conductivity, good flexibility and mechanical strength. The inventor has found through research that the use of the CeO2-modified current collector of the present invention in a negative electrode-free sodium ion battery can improve the mechanical properties of the pole piece, so that the negative electrode can not be electrically separated under the action of volume expansion stress, effectively reducing the probability of sodium metal forming dendrites to cause volume expansion, and improving the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 It is a comparison chart of the normal temperature cycle performance between Comparative Example 1-2 and Example 1;

[0026] Figure 2 It is a comparison chart of high temperature cycle performance between comparative example 1-2 and embodiment 1. DETAILED DESCRIPTION

[0027] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but it will be appreciated by those skilled in the art that the following embodiments and examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified, proceed according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0028] In a first aspect, the present invention provides a CeO2-modified current collector, comprising a current collector and a CeO2 layer coated on the current collector;

[0029] The CeO2 layer includes CeO2 nanowires and a binder;

[0030] The mass proportion of CeO2 nanowires in the CeO2 layer is 96%-99%, preferably 98%.

[0031] CeO2 has an extremely high aspect ratio, good electrical conductivity, good flexibility and mechanical strength. The inventors have found that using the CeO2-modified current collector of the present invention in a negative electrode-free sodium ion battery can improve the mechanical properties of the electrode sheet, so that the negative electrode will not be electrically separated under the action of volume expansion stress, and the probability of volume expansion caused by the formation of sodium metal dendrites is effectively reduced.

[0032] In addition, CeO2 can withstand higher temperatures. Modifying it on the surface of the current collector will not affect the battery performance, but will increase the high temperature resistance of the aluminum foil and improve the high temperature cycle life of the battery cell. CeO2 does not swell in organic solvents. Modifying it on the surface of the current collector has a stable structure and can prevent the sodium ion battery from changing in volume during the cycle.

[0033] In some optional embodiments, the diameter of the CeO2 nanowire is 2-6 nm, and the aspect ratio is 100-500.

[0034] CeO2 nanowires have better flexibility and mechanical strength than CeO2 nanoparticles.

[0035] In some optional embodiments, the binder includes but is not limited to PVDF.

[0036] In some optional embodiments, the coating density of the CeO2 layer is 6 to 8 g / cm 2 (The coating density refers to the coating density of CeO2 nanowires and binder in the CeO2 layer).

[0037] In some optional embodiments, the current collector includes aluminum foil or carbon-coated aluminum foil.

[0038] In a second aspect, the present invention provides a method for preparing the above-mentioned CeO2 modified current collector, comprising: preparing a slurry containing CeO2 nanowires and a binder, then coating the slurry on the current collector, and preparing the CeO2 modified current collector after drying.

[0039] The preparation method is simple and convenient, and the prepared CeO2-modified current collector can be used in a negative electrode-free sodium ion battery to effectively improve the cycle performance of the battery and extend the service life of the battery.

[0040] In some optional embodiments, the slurry further contains a dispersant;

[0041] The dispersant includes but is not limited to NMP, or other dispersants known in the art that can improve the CeO2 nanowires.

[0042] In some optional embodiments, the mass concentration of NMP in the slurry is 0.1%.

[0043] In a third aspect, the present invention provides the use of the above-mentioned CeO2-modified current collector in the preparation of a sodium ion battery.

[0044] The CeO2-modified current collector provided by the present invention is used in a sodium ion battery, which can effectively improve the electrochemical performance of the battery and extend the service life of the battery.

[0045] In a fourth aspect, the present invention provides a sodium ion battery using the above-mentioned CeO2 modified current collector as the negative electrode.

[0046] The sodium ion battery provided by the invention has good electrochemical properties and a long service life.

[0047] The present invention is further described below by means of specific examples and comparative examples. However, it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.

[0048] It should be noted that, in the present invention, the diameter of the cerium dioxide nanowires is 2-6 nm, the aspect ratio is 100-500, and they were purchased from Jiangsu Xianfeng Nanomaterials.

[0049] Example 1

[0050] A CeO2 modified current collector, the preparation method is as follows:

[0051] Cerium dioxide nanowires, NMP and PVDF were mixed (wherein the mass proportion of cerium dioxide nanowires was 97.9%, the mass proportion of NMP was 0.1%, and the mass proportion of PVDF was 2%), and then the slurry was coated on a 12 μm thick aluminum foil with a scraper, and then the current collector was dried at 60°C and rolled to prepare a CeO2-modified current collector. The coating density of the CeO2 layer on the current collector was 7 g / cm 2 .

[0052] Example 2

[0053] A CeO2 modified current collector, the preparation method is as follows:

[0054] Cerium dioxide nanowires, NMP and PVDF were mixed (wherein the mass proportion of cerium dioxide nanowires was 97.9%, the mass proportion of NMP was 0.1%, and the mass proportion of PVDF was 2%), and then the slurry was coated on a 12 μm thick aluminum foil with a scraper, and then the current collector was dried at 60°C and rolled to prepare a CeO2-modified current collector. The coating density of the CeO2 layer on the current collector was 8 g / cm 2 .

[0055] Example 3

[0056] A CeO2 modified current collector, the preparation method is as follows:

[0057] Cerium dioxide nanowires, NMP and PVDF were mixed (wherein the mass proportion of cerium dioxide nanowires was 96%, the mass proportion of NMP was 0.1%, and the mass proportion of PVDF was 3.9%), and then the slurry was coated on a 12 μm thick aluminum foil with a scraper, and then the current collector was dried at 60°C and rolled to prepare a CeO2-modified current collector. The coating density of the CeO2 layer on the current collector was 6 g / cm 2 .

[0058] Example 4

[0059] A CeO2 modified current collector, the preparation method is as follows:

[0060] Cerium dioxide nanowires, NMP and PVDF were mixed (wherein the mass proportion of cerium dioxide nanowires was 98.9%, the mass proportion of NMP was 0.1%, and the mass proportion of PVDF was 1%), and then the slurry was coated on a 12 μm thick aluminum foil with a scraper, and then the current collector was dried at 60°C and rolled to prepare a CeO2-modified current collector. The coating density of the CeO2 layer on the current collector was 8 g / cm 2 .

[0061] Comparative Example 1

[0062] A carbon-coated aluminum foil has a thickness of 12 μm, an aluminum foil thickness of 10 μm, and a carbon-coated layer thickness of 2 μm.

[0063] Comparative Example 2

[0064] A current collector, which differs from Example 1 in that the cerium dioxide nanowires are replaced with an equal amount of cerium dioxide nanoparticles, the particle diameter of which is 10-20 nm and is purchased from Jiangsu Xianfeng Nanomaterials.

[0065] Test Example 1

[0066] The current collectors provided in the above examples and comparative examples were sliced ​​into small discs with a diameter of 14 mm and dried in vacuum at 120° C. for 16 h. The treated current collectors were then used as negative electrodes and assembled with sodium iron pyrophosphate positive electrodes and electrolytes to form C2032 button-type full batteries.

[0067] Among them, the composition of the sodium iron pyrophosphate positive electrode sheet is: 95.4% PN-01 (polyanion) + 1.8% PVDF-5130 (glue) + 1.2% SP (conductive carbon black) + 1.2% CNT (carbon nanotube) + 0.4% HFF-2918 (dispersant);

[0068] The electrolyte composition is: 14% NaPF6 + 84% diethylene glycol dimethyl ether.

[0069] The above batteries were subjected to electrochemical performance tests (first charge specific capacity, first discharge specific capacity, first efficiency and 100-cycle capacity retention rate):

[0070] Cycle test: All batteries are first converted to 0.5C capacity with 0.2C current, and then cycle tested. The charge and discharge range is 2.0-3.3V, and the current is 0.5C / 1C.

[0071] The results of the first charge specific capacity, first discharge specific capacity, first efficiency and 100-cycle capacity retention rate are shown in Table 1.

[0072] Table 1 Electrical performance of full cells assembled with different current collectors

[0073]

[0074] The batteries of Example 1 and Comparative Examples 1-2 were subjected to normal temperature charge-discharge cycles and high temperature charge-discharge cycles, respectively. The results are as follows: Figure 1 and Figure 2As shown. In normal temperature cycle, the capacity retention rate of comparative example 1 is 79.99% @ 196cls (meaning that after 196 cycles of charge and discharge of the battery, the capacity retention rate is 79.99%, the same below), the capacity retention rate of comparative example 2 is 86.1% @ 196cls, and the capacity retention rate of embodiment 1 is 88.15% @ 380cls; in 45°C high temperature cycle, the capacity retention rate of comparative example 1 is 68.75% @ 194cls, the capacity retention rate of comparative example 2 is 84.04% @ 197cls, and the capacity retention rate of embodiment 1 is 88.18% @ 228cls, indicating that the normal and high temperature cycle performance of embodiment 1 are better than those of comparative examples 1 and 2.

[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A CeO2-modified current collector, characterized in that: It includes a current collector and a CeO2 layer coated on the current collector; The CeO2 layer includes CeO2 nanowires and a binder; The mass proportion of CeO2 nanowires in the CeO2 layer is 96%-99%.

2. The CeO2-modified current collector according to claim 1, characterized in that: The diameter of the CeO2 nanowire is 2-6nm, and the aspect ratio is 100-500.

3. The CeO2 modified current collector according to claim 1, characterized in that: The binder includes PVDF.

4. The CeO2 modified current collector according to claim 1, characterized in that: The coating density of the CeO2 layer is 6-8 g / cm 2 .

5. The CeO2 modified current collector according to claim 1, characterized in that: The current collector includes aluminum foil or carbon-coated aluminum foil.

6. The method for preparing a CeO2-modified current collector according to any one of claims 1 to 5, characterized in that: include: A slurry containing CeO2 nanowires and a binder is prepared, and then the slurry is coated on a current collector, and a CeO2-modified current collector is prepared after drying.

7. The preparation method according to claim 6, characterized in that: The slurry also contains a dispersant; The dispersant includes NMP.

8. Use of the CeO2 modified current collector according to any one of claims 1 to 5 in the preparation of a sodium ion battery.

9. A sodium ion battery, characterized in that: The CeO2 modified current collector according to any one of claims 1 to 5 is used as the negative electrode.

Citation Information

Patent Citations

  • High-surface-energy coating liquid for current collector and application of high-surface-energy coating liquid

    CN114530605A

  • Negative current collector of negative-electrode-free lithium metal battery as well as preparation method and application of negative current collector

    CN115064700A

  • Current collector, secondary battery, battery module, battery pack, and electric device

    CN118472265A

  • Current collector, secondary battery, battery module, battery pack, and electric device

    CN118507733A